PERUBAHAN SIFAT-SIFAT BIOKIMIAWI, FISIKAWI, MIKROBIAWI, DAN SENSORIS PRODUK "WADI" IKAN BETOK (Anabas testudineus Bloch) = BIOCHEMICAL, PHYSICAL, MICROBIOLOGICAL AND SENSORY CHANGES OF "WADI" WALKING FISH - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT "Wad?' is a traditional fermented fish product originally from South Kalimantan. This research was conducted to study the changes of biochemical, physical, microbiological and sensory properties of "wadi" during processing. "Wadi" was made from "Betok" fish (Anabas testudineus Bloch) using high concentration of salt. In this study, "Wadi" was made using salt concentrations of 25% wlw and 10% w/w for 12 weeks and 14 days fermentation respectively. The results showed that during 14 days fermentation, "Wadi" with 25% w/w salt decreased its water content and soluble nitrogen meanwhile NaCI and ash contents increased sharply in the first day and then relatively stable in the following days. The fish meat hardness increased continuously and TVB values relatively constant during 14 days of fermentation. Observation for 12 weeks salting process showed that the highest NaC1 level and hardness value achieved in three weeks, water content started to increase after three weeks and TVB value reached 32,38 mg N/100 g sample in six weeks. Based on water content, NaCI content, TVB value and fish meat hardness, the best "wadi" was achieved after three weeks of salt fermentation. Bacteria that played essential role in "wadi" processing was halophylic bacteria, which have proteolytic activity. "Wad?' using 10% salt level showed the deterioration at the seventh day of salt fermentation process.